Electropolymers of 4-(thieno[3, 2-b]thiophen-3-yl)benzonitrile extended with thiophene, 3-hexylthiophene and EDOT moieties; their electrochromic applications. (19th November 2021) - Demirtas, Ilknur; Ertas, Erdal; Topal, Sebahat; Ozturk, Turan
Abstract: Three new π-conjugated 4-(thieno[3, 2- b ]thiophen-3-yl)benzonitrile based monomers having thiophene, 3-hexylthiophene and EDOT at the peripherals were synthesized. Their electropolymerization produced the corresponding electroactive polymers, P1, P2, and P3, which exhibited electrochromic properties with color developments from red to blue, orange-yellow to pale-blue, and purple to pale-grey, respectively. Functional design of the monomers with electron deficient benzonitrile at ß-position of thieno[3, 2- b ]thiophene (TT) and electron-rich thienyl groups at the peripherals influenced the HOMO and LUMO levels and, thereby, reduced the band gap of the conjugated polymers. Considering the band gaps of electropolymerized TT based polymers in the literature, the polymer P3, obtained through electropolymerization, had a comparable band gap of 1.73 eV. Electrochromic devices (ECD) of the new polymers displayed different optical contrasts (ΔT%) of 20% at 507 nm, 25% at 443 nm, and 34% at 579 nm for P1/ PProDOP, P2 /PProDOP, and P3 /PProDOP, respectively. Furthermore, they had modest switch times of 1.2–1.7 s for bleaching and 0.9–1.7 s for coloring. Of the polymers, P3/ PProDOP, bearing EDOT moieties, had a reasonable coloration efficiency (CE) of 240 cm 2 /C at 579 nm, excellent permanent memory effect, and high stability of color switch, retaining 88% of its electroactivity after 500 cycles, switching at the applied voltages of −0.2 and + 1.1 V. Graphical abstract: Image 1 Highlights: Thieno[3, 2- b ]thiophenes with different substituents of Th, Hexyl-Th and EDOT exhibit different colors. Cyclic stability of 88% after 500 cycle. Low band gap of 1.73 V. High coloration efficiency of 240 cm 2 C -1 . Stable color after removing the voltage.